2016
DOI: 10.1007/s10265-016-0883-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of snRNAs and its significance for plant development

Abstract: Small nuclear RNA (snRNA) represents a distinct class of non-coding RNA molecules. As these molecules have fundamental roles in RNA metabolism, including pre-mRNA splicing and ribosomal RNA processing, it is essential that their transcription be tightly regulated in eukaryotic cells. The genome of each organism contains hundreds of snRNA genes. Although the structures of these genes are highly diverse among organisms, the trans-acting factors that regulate snRNA transcription are evolutionarily conserved. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 82 publications
0
28
0
Order By: Relevance
“…In the SRD2‐dependent pathway, both CPL4 RNAi and srd2‐1 compromised snRNA biogenesis (Ohtani and Sugiyama, ; Fukudome et al ., ). However, because the effect of CPL4 RNAi by itself on the total snRNA level was negligible under the standard conditions (Fukudome et al ., ), the inhibitory effects might become significant only in limited processes, such as the formation of the auxin gradient at the developing LRP (Ohtani et al ., ; Ohtani, ). When combined with the srd2‐1 mutation, however, the CPL4 RNAi srd2‐1 calli were no longer able to proliferate at the restrictive temperature (Figure S4), suggesting that the level of functional snRNA pool might have dropped below the threshold to sustain the cell proliferation (Ohtani et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In the SRD2‐dependent pathway, both CPL4 RNAi and srd2‐1 compromised snRNA biogenesis (Ohtani and Sugiyama, ; Fukudome et al ., ). However, because the effect of CPL4 RNAi by itself on the total snRNA level was negligible under the standard conditions (Fukudome et al ., ), the inhibitory effects might become significant only in limited processes, such as the formation of the auxin gradient at the developing LRP (Ohtani et al ., ; Ohtani, ). When combined with the srd2‐1 mutation, however, the CPL4 RNAi srd2‐1 calli were no longer able to proliferate at the restrictive temperature (Figure S4), suggesting that the level of functional snRNA pool might have dropped below the threshold to sustain the cell proliferation (Ohtani et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although C. canephora genome size is similar to the size of Proteus vulgaris and Berberis vulgaris genomes, evolutionary differences and applied methodologies should be taken into account before any comparison. [26], which is crucial since it increases diversity. In plants, the extension of the alternative splicing process can reach over 60% of intron-containing genes [27].…”
Section: Non-coding Rna Loci Overviewmentioning
confidence: 99%
“…Figure 2 shows a current model of Sm class snRNP assembly in mammalian cells. snRNP biogenesis is initiated by transcription of snRNAs through a complex called SNAPc (snRNA activating protein complex) ( Figure 2 ; reviewed by Hernandez, 2001 ; Will and Lührmann, 2011 ; Matera and Wang, 2014 ; Ohtani, 2017 ). As for mRNAs transcribed by RNA polymerase II, the 5′ capping and 3′ cleavage of Sm class UsnRNAs occurs in a co-transcriptional manner.…”
Section: Current Model Of Spliceosomal Snrnp Assembly Based On Mammalmentioning
confidence: 99%
“…Mutations of LSM4 and LSM5, which encode essential core proteins of Sm-like class snRNPs ( Figure 2 ; Achsel et al, 1999 ), and of Tgs1, which hypermethylates the 5′ cap of snRNAs ( Figure 2 ; Mouaikel et al, 2002 ), were reported to enhance plant sensitivities to abiotic stresses, such as salt, drought, and cold stress ( Xiong et al, 2001 ; Zhang et al, 2011 ; Gao et al, 2017 ). Moreover, SHOOT REDIFFERENTIATION DEFECTIVE 2 (SRD2), a subunit of the snRNA-specific transcription activator complex, SNAPc ( Figure 2 ), is required for in vitro dedifferentiation and organogenesis ( Ohtani and Sugiyama, 2005 ; Ohtani et al, 2015 ; Ohtani, 2015 , 2017 ). The disorders of the corresponding mutants can be explained by the misregulation—due to altered RNA processing—of specific genes involved in key processes, i.e., circadian rhythms, stress responses, and auxin polar transport ( Xiong et al, 2001 ; Deng et al, 2010 ; Hong et al, 2010 ; Ohtani et al, 2010 ; Sanchez et al, 2010 ; Zhang et al, 2011 ; Schlaen et al, 2015 ).…”
Section: Roles For the Nucleolus And Cajal Bodies In Spliceosomal Snrmentioning
confidence: 99%